PERFECTING OF THE METALLURGICAL REGIME OF MELTING OF SYNTHETIC CAST-IRON BY DOPLEX-PROCESS INDUCTION MELTING FURNACE - INDUCTION MIXER-DISTRIBUTION DEVICE - D. A. Volkov; V. I. Rassudov; S. N. Shket; R. I. Trubitskij; A. D. Volkov; A. S. Glamazdin (Литьë и металлургия)
The investigations of melting practice and thermo-time hold of the synthetic cast iron in the induction furnaces and mixer-distribution device, out-of-furnace development of liquid melt and filling it into tiling chills are carried out.